CHARACTER ASSOCIATION AND PATH COEFFICIENT ANALYSIS FOR YIELD AND ITS COMPONENT TRAITS IN RICE LANDRACES OF BIHAR - SMRITI,; S. P. SINGH,; MANKESH KUMAR,; R. K. VERMA,; RISHAV KUMAR,; KUMARI NEHA, (The Bioscan, 2015)
An investigation was carried out in 16 rice genotypes including 13 local landraces of Bihar to understand association among 13 contributing traits for yield and their direct and indirect influence on grain yield. The correlation analysis indicated that genotypic correlation coefficient was higher than their respective phenotypic correlation coefficient. Grain yield/ha was found significantly and positively correlated with number of grains/ panicle (0.546, 0.454) and significantly but negatively correlated with plant height (-0.840, -0.727) at both genotypic and phenotypic level respectively. Path coefficient analysis revealed that kernel breadth (1.810) had high positive direct effect on grain yield followed by kernel L/B ratio (1.357), number of grains/panicle (1.309), panicle length (0.362), 1000 grain weight (0.313), number of tillers/hill (0.186) and panicles/m 2 (0.087). Hence, selection based on traits like number of grains/panicle could bring improvement in paddy yield in these rice genotypes.